Changes in Somatic Cell Count, Composition and Cytokine Levels in Milk from Cows with Mastitis Due to Mixed Infections - Safak, Tarik; Risvanli, Ali (Univ Fed Rio Grande Do Sul, 2021)
Background: Mastitis is a mammary gland inflammation that is very common worldwide, mostly caused by bacteria, and causes enormous economic losses. Many microorganisms cause this disease. The most common causes of mastitis by these microorganisms are Staphylococcus aureus (S. aureus), Escherichia coli (E. coli) and Streptococcus agalactiae (S. agalactiae). The anti-inflammatory properties of transforming growth factor (TGF)-beta include: 1) limiting interferon (IFN)-gamma production; 2) increasing the expression of the interleukine (IL)-1 receptor antagonist; 3) inhibiting macrophage production of chemokines, pro-inflammatory cytokines, nitric oxide, and reactive oxygen intermediates; and 4) increasing macrophage clearance of bacterial debris and damaged parenchymal cells. It is stated that cytokines and milk composition change in case of mastitis. In this study, it was aimed to reveal the changes in milk TGF-beta 1 and Tumor necrosis factor (TNF)-alpha concentrations and milk composition in mixed infections caused by three pathogens causing mastitis. Materials, Methods & Results: In this study, milk samples from 90 cows were divided into 5 groups. Tumor necrosis factor (TNF)-alpha and TGF-beta 1 concentrations and milk composition were determined in these milk samples. The California Mastitis Test (CMT) was applied to the cows included in the study and scoring was done. According to the CMT results of the milk samples taken, CMT(-) cows were included in group 1 (n = 22). Those with the CMT(+) were sent to the microbiology laboratory for analysis within 2 h. After the bacteria was determined, combination groupings were formed. Group 2 (n = 17), in which S. aureus and E. coli grew together, group 3 (n = 21), in which S. aureus and S. agalactiae grew together, group 4 (n = 8), in which S. agalactiae and E. coli grew together in milk samples, and milk samples without any bacterial growth in CMT (+) formed group 5 (n = 22), respectively. Somatic cell count was measured with the DeLaval Cell Counter((R)) (Cell Counter DCC) device. Mineral matter, fat, protein, lactose, electrical conductivity and specific gravity were measured in milk samples using Lactoscan Milk Analyzer (Milkotronic/EUROPE). Milk samples were then stored at -80 degrees C to measure TGF-beta 1 and TNF-alpha. Tumor necrosis factor-alpha and TGF-beta 1 concentrations in milk samples were measured using ELISA kits (Sunred Biological Technology). Discussion: Changes in milk TNF-alpha and TGF-beta 1 concentration and milk composition were determined in milk samples with mastitis caused by mixed infection. The TNF-alpha concentration of group 4 was higher than the other groups. On the other hand, the highest concentration of TGF-beta 1 was found in group 2. While the number of somatic cells in group 1 was lower than in groups 2, 3, and 4, there was no statistical difference between groups 1 and 5. The lowest milk fat ratio was found in group 1, and it was found to be statistically lower than groups 2, 3, and 4. While the rate of solid-non-fat of group 1 increased compared to groups 2 and 3, the highest protein ratio was found in groups 1 and 5. There was no difference between the 5 groups in terms of mineral matter ratios. While the specific gravity was highest in group 1, there was no statistical difference between the other 4 groups. Overall, it was concluded that there was an increase in TNF-alpha and TGF-beta 1 concentrations and a change in milk composition in samples with bacterial growth.
Keywords: bovine mastitis; cytokine; milk composition; raw milk; transforming growth factor